Fundamentals of pruning - Joe Clokey; Jora Clokey; Rick Keller; Carrie Filler; San Luis Video Publishing (Los Osos, CA : San Luis Video Pub., 2000)
Describes the benefits of skillful pruning for various flowers and trees. Topics include why and how plants respond to pruning, proper tool selection and use, why and when to prune, and pruning for desired results.
Keywords: Pruning